MENTALISATION AND PSYCHOSOMATICS - Tsenkov, Boyko (E-Journal VFU, 2024)
The article presents a comparative analysis of the French model for understanding mentalization and Peter Fonagy and Mary Target’s theory of reflective functioning in the context of psychosomatic conditions. Similarities and differences between the two theories of mentalizing in the context of psychosomatics are discussed.